Challenges and Opportunities for Sharia Cooperatives in Encouraging the Growth of Sharia MSMEs in the Digital Era - Elvira Fitriyanti (Journal of Sharia Micro Enterprise and Cooperation, 2024)
Digital transformation has become an important factor in increasing economic competitiveness, especially for Islamic MSMEs facing increasingly fierce global competition. However, Islamic cooperatives, which act as the main drivers of Islamic MSMEs in Indonesia, still face various challenges in adopting digital technology. This study aims to analyze the challenges and opportunities faced by Islamic cooperatives in driving the growth of Islamic MSMEs in the digital era. A qualitative approach with a descriptive method was used in this study, with data collected through in-depth interviews and literature studies. The research sample consisted of Islamic cooperative administrators and Islamic MSME managers involved in the digitalization process in various regions of Indonesia. The results of the study show that Islamic cooperatives face significant challenges in terms of infrastructure, digital literacy, and access to financing for digital transformation. However, digitalization also offers great opportunities for Islamic cooperatives to improve operational efficiency, expand market access, and provide faster services for Islamic MSMEs. The conclusion of this study shows that a strategic partnership between Islamic cooperatives, the government, and digital financial institutions can be a solution to overcome barriers to digitalization and maximize the potential of Islamic MSMEs in Indonesia.